A cross-sectional survey of orthopaedicians to understand the prescribing pattern of disease modifying osteoarthritis drugs in osteoarthritis - Saini, Naveen; Rawat, Santosh; Saresa, Hiten; Mehta, Kapil Dev; Jain, Rishi (International Journal of Research in Orthopaedics, 2019)
Background: Numerous dietary supplements with disease-modifying action are available in Indian market. However, doctor’s preferences for these disease modifying osteoarthritis drugs (DMOADs) to prevent progression of OA are not known. The objective of this study was to quantify doctor preferences for potential DMOADs. Methods: The survey instrument (online survey questionnaire at survey monkey) was developed by researchers upon review of existing literature and detailed discussion with practicing clinicians. Face and content validity and reliability (test-retest method) was assessed through a focused panel of clinicians to determine if content was adequate to obtain the necessary data. This was a cross-sectional digital survey of 207 orthopaedicians during Indian Orthopaedic Association Conference-2018 organized at Coimbatore. Results: NSAIDs + DMOAD combinations were the most preferred treatment option for newly diagnosed OA patients. 44% orthopaedicians prefer to start the treatment with combination of NSAID and DMOAD as compared to 10% with paracetamol monotherapy. Glucosamine/chondroitin combinations are the most commonly preferred DMOAD by the orthopaedicians; followed by undenatured type II collagen. 66% of the doctors surveyed opined that the efficacy of undenatured type-II collagen is better as compared to other DMOADs. Conclusions:The findings from the survey suggest that majority of orthopaedicians prefer to prescribe NSAID with DMOAD combinations for newly diagnosed osteoarthritis patients.